(untitled) (Journal of the College of Education for Women, 2019)
The present study is an attempt to show how the three Umayyad poets ; Jarir , Al-Farazdaq and Al-Akhtal have consciously and skillfully employed in their poetry som ancientArab legends ,historical events and wars as they provide atrue image of the values andcustoms of the peoples who lived before them .Their employed , how ever, takes avarying degrees depending, to alarge extent , an thevast but personal knowledge of each poet the past tradition , and practices . Jarir ,in manyrespects out , stands the first , Al-Farazdaq , the second and Al-Akhtal , the third .